2012 IEEE International Geoscience and Remote Sensing Symposium 2012
DOI: 10.1109/igarss.2012.6351519
|View full text |Cite
|
Sign up to set email alerts
|

A discriminative-generative approach to the characterization of subsurface contaminant source zones

Abstract: Large-scale contamination of ground water due to improper disposal of hazardous chemicals poses a global threat to drinking water supplies. Effective restoration and remediation of such sites relies upon a knowledge of the contaminant's distribution within the subsurface. Obtaining a detailed map of the existing distribution is usually not feasible; rather partial knowledge in terms of certain metrics that characterize the distribution has recently been shown to be sufficient for planning and monitoring remedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…We have used the MoE model to estimate a suitable discretization of the metric and in this work we have specifically shown that it can be effectively used for predicting the percentage-mass of DNAPL in pools from the down-gradient concentration profiles. Comparing to our preliminary work [2] where we used Gaussians to model the bin distribution, we get similar accuracies and bin ranges but the overlap between bins is considerably smaller. In the future we would like to compare the effectiveness of this approach against more sophisticated methods that explicitly force bins to be disjoint and also measure its performance against regression based on the traditional MoE model.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We have used the MoE model to estimate a suitable discretization of the metric and in this work we have specifically shown that it can be effectively used for predicting the percentage-mass of DNAPL in pools from the down-gradient concentration profiles. Comparing to our preliminary work [2] where we used Gaussians to model the bin distribution, we get similar accuracies and bin ranges but the overlap between bins is considerably smaller. In the future we would like to compare the effectiveness of this approach against more sophisticated methods that explicitly force bins to be disjoint and also measure its performance against regression based on the traditional MoE model.…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, the corresponding metric values for that group define the extent of the bin in metric space. In previous work we modeled bin distributions using Gaussians, which can lead to large overlap [2]. So, to obtain bins in metric space that minimally overlap, we model the distribution of metric values in the k-th bin using the following function:…”
Section: Mixture Of Experts For Metric Discretizationmentioning
confidence: 99%
See 1 more Smart Citation